2018
DOI: 10.7554/elife.35786
|View full text |Cite
|
Sign up to set email alerts
|

Human axial progenitors generate trunk neural crest cells in vitro

Abstract: The neural crest (NC) is a multipotent embryonic cell population that generates distinct cell types in an axial position-dependent manner. The production of NC cells from human pluripotent stem cells (hPSCs) is a valuable approach to study human NC biology. However, the origin of human trunk NC remains undefined and current in vitro differentiation strategies induce only a modest yield of trunk NC cells. Here we show that hPSC-derived axial progenitors, the posteriorly-located drivers of embryonic axis elongat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
162
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(189 citation statements)
references
References 115 publications
21
162
1
Order By: Relevance
“…Avian studies have reported that RA participates in NC migration, and possibly formation (Martínez-Morales et al, 2011), but murine knockout models affecting RA signaling still form NC (Dupé and Pellerin, 2009;Niederreither et al, 2000). Here, we find that, similar to other reports (Fattahi et al, 2016;Frith et al, 2018;Fukuta et al, 2014;Huang et al, 2016;Mica et al, 2013), exogenous RA can posteriorize NCs during maturation stages. However, early addition of RA prevents NC specification.…”
Section: Putative Additional Players Triggered By Chir99021supporting
confidence: 92%
See 1 more Smart Citation
“…Avian studies have reported that RA participates in NC migration, and possibly formation (Martínez-Morales et al, 2011), but murine knockout models affecting RA signaling still form NC (Dupé and Pellerin, 2009;Niederreither et al, 2000). Here, we find that, similar to other reports (Fattahi et al, 2016;Frith et al, 2018;Fukuta et al, 2014;Huang et al, 2016;Mica et al, 2013), exogenous RA can posteriorize NCs during maturation stages. However, early addition of RA prevents NC specification.…”
Section: Putative Additional Players Triggered By Chir99021supporting
confidence: 92%
“…The co-expression of TBXT along with SOX2 defines neuromesodermal progenitors (NMPs) that contribute to posterior axial tissues, including spinal cord and mesoderm (Henrique et al, 2015). Importantly, NMPs have also been suggested to contribute to NCC formation (Cambray and Wilson, 2007;McGrew et al, 2008;Wymeersch et al, 2016), and recently NCs have been generated from NMPs (Frith et al, 2018). Therefore, we evaluated the expression of SOX2 and TBXT in high-WNT cultures.…”
Section: Posterior Nccs Transiently Express An Nmp-like Precursor Promentioning
confidence: 99%
“…It was recently shown that NMPs produced from hPSCs in vitro have the potential to generate NCCs (Frith et al, 2018), and in a manuscript submitted elsewhere by Hackland et al we have found that posterior NC generated in a xeno-free (BSA free, and using N2 instead of B27 supplement, and under modulated BMP) platform are also derived from a similar axial progenitor. Some recent evidence from lineage tracing experiments in chick and mice favor the contribution of NMPs to NCCs (Cambray and Wilson, 2007; McGrew et al, 2008; Wymeersch et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
“…HOX genes define the tempo of the induction (Bel-Vialar et al, 2002;Del Corral and Storey, 30 2004;Deschamps and Duboule, 2017;Ebisuya and Briscoe, 2018;Lippmann et al, 2015;31 Mazzoni et al, 2013;Wymeersch et al, 2019). This might result in the current limited control 32 over pluripotent stem cells (PSCs) differentiation into caudal cell types of distinct well-defined 33 rostro-caudal identities (Diaz-Cuadros et al, 2020;Du et al, 2015;Duval et al, 2019;Faustino 34 Martins et al, 2020;Frith et al, 2018;Gouti et al, 2014;Li et al, 2005;Lippmann et al, 2015;35 Matsuda et al, 2020;Maury et al, 2015;Ogura et al, 2018;Peljto et al, 2010;Verrier et al, 36 2018). Indeed, the two models imply different strategies to control in vitro PSC differentiation.…”
Section: Introduction 15mentioning
confidence: 99%